An update of the classical Bokhman’s dualistic model of endometrial cancer - Wilczyński, Miłosz; Danielska, Justyna; Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2016)
According to the classical dualistic model introduced by Bokhman in 1983, endometrial cancer (EC) is divided into two basic types. The prototypical histological type for type I and type II of EC is endometrioid carcinoma and serous carcinoma, respectively. The traditional classification is based on clinical, endocrine and histopathological features, however, it sometimes does not reflect the full heterogeneity of EC. New molecular evidence, supported by clinical diversity of the cancer, indicates that the classical dualistic model is valid only to some extent. The review updates a mutational diversity of EC, introducing a new molecular classification of the tumour in regard to data presented by The Cancer Genome Atlas Research Network (TGCA).